Promoting character development in primary school: A moral education approach - Nida Amelia Efendi; Siti Masyithoh; Warda Helwiyah (Yayasan Azhar Amanaa Yogyakarta, 2024)
This research is motivated by indications of behavior that shows the low moral quality of students in Indonesia, so there is a need for moral education from an early age which must be applied to the importance of moral education with Pancasila values in forming the character of students in elementary schools. This research discusses moral education which has an important role in developing students' awareness of good values and shaping behavior that is in accordance with norms. Pancasila values consist of five principles that reflect the nation's personality. A gradual approach and understanding of goodness are important in forming students' character through moral education. This research is a type of literature review research with the collection of information used in the research obtained through previous research, citations, journals and books that are relevant to the research topic.